Power: Essential works of Foucault 1954-1984: Volume 3 - Foucault, Michel 1926-1984; Faubion, James D. (London Penguin Books, 1994)
Few philosophers have had as strong an influence on the twentieth century as Michel Foucault. His work has affected the teaching of any number of disciplines and remains, twenty years after his death, critically important. This newly available edition is drawn from the complete collection of all of Foucault's courses, articles, and interviews, and brings his most important work to a new generation of readers.Power (edited by James D. Faubion) draws together Foucault's contributions to what he saw as the still-underdeveloped practice of political analysis. It covers the domains Foucault helped to make part of the core agenda of Western political culturemedicine, psychiatry, the penal system, and sexuality.